Особливості логістичного забезпечення танспортування військових вантажів - Поляков, Андрій; Терещенко, Олександр; Гунько, Ірина (Посвіт, 2019)
At actual autothechnogo protection of military units there is a complex task of control of the system in its entirety. The use of logistic systems for managing material and information processing needs the development of adequate mathematical models. The general rules for the modification of road transport of military goods, which take into account the specifics of the activity of the armed forces, are under investigation.
Peculiarities of logistic characterization of transmission of load cargoes
Keywords: 656.078